Studi Kasus: Implementasi Pemberian Terapi Bermain Balok pada Anak Stunting di Desa Kemutug Kidul - Fitriani, Gita Salsa Viera; Purnamasari, Meivita Dewi; Nani, Desiyani (Journal of Bionursing, 2025)
Background. Stunting is a growth disorder due to chronic malnutrition and/or chronic or recurrent infectious diseases as indicated by the z-score of height for age (TB/U). Accordig to WHO, children with stunting can cause developmental disorders such as gross motor, fine motor, language and social disorders. Fine motor development is relate to the development ability to use the fingers to carry out various activities. For example, the ability to move objects from hand, scribble, arrange block, cut, write and etc. Methods. Case study by implementation based on evidance based practice in nursing care Results. Motor development in children can be increased by using block play therapy. Playing with block trains children to be able to move the small muscles in their hand and trans coordination between eye and hand movement Conclusion. The application of block play therapy in writing this final scientific work can improve fine motor aspect in preschool aged children.